The Effectiveness of YOPI (Yoga and Lavender Aromatherapy) in Reducing Menstrual Pain (Dysmenorrhea) in Young Women in Mekarbhuana Village, Badung - I Gusti Agung Manik Karuniadi; Luh Putu Widiastini; Putu Ayu Dina Saraswati (Poltekkes Kemenkes Semarang, 2023)
Background: Menstrual pain (dysmenorrhea) is pain/cramps in the abdomen that occurs on the first and second day of menstruation, has a distinctive characteristic, which appears regularly and periodically. adolescents who experience dysmenorrhea, have an impact on tension, fatigue, and emotional conflict within themselves. Dysmenorrhea can be treated with pharmacological and non-pharmacological therapy. Providing yoga and aromatherapy which are included in non-pharmacological therapy, not only provide good physical benefits for young women but also affect their psychological condition Methods: The research design was pre-experimental with a one group pretest-posttest design, with a total sample of 36 young women. Results: The pain scale before being given the yoga intervention and lavender aromatherapy was given an average of 3.9 in the moderate pain category. After the intervention was given, there was a decrease in the pain scale to 1.4 in the mild pain category. The Wilcoxon test was used for bivariate analysis of pain before and after intervention because the data were not normally distributed. The results of the bivariate test conducted obtained a p value of 0.000. Conclusion: Yoga and Lavender Aromatherapy are effective for reducing menstrual pain (dysmenorrhea) in young women in Mekarbhuana Village